Pengaruh Citra Merek, Persepsi Harga, Kualitas Layanan dan Persepsi Kualitas terhadap Keputusan Pembelian Konsumen iPhone di Semarang - Silviana, Silviana; Purwanto, Edy; Baskara, Andika (Jurnal Maksipreneur, 2025)
This study aims to investigate the influence of brand image, price perception, service quality, and perceived quality on consumer iPhone purchasing decisions in Semarang. The study population consists of iPhone users in the city. The sampling method used was non-probability sampling with a purposive sampling technique, which resulted in 105 respondents as the research sample. Data were collected through online questionnaire distribution. Data analysis was carried out using the multiple linear regression analysis method to test the relationship between independent variables (brand image, price perception, service quality, and perceived quality) and the dependent variable (purchase decision). The results showed that brand image, price perception, service quality, and perceived quality have a positive and significant influence on consumer purchasing decisions. These findings provide strong empirical evidence of the important role of brand image, price perception, service quality, and perceived quality in shaping consumer iPhone purchasing decisions in Semarang. The practical implications of this study emphasize the importance for companies to pay attention to and improve these aspects in their marketing strategies to attract and retain consumers. This study also contributes to the enrichment of the literature on consumer behavior and marketing strategy.